(untitled) (Historia, 2021)
This study of the central battleground of white extra-parliamentary politics in the 1950s is the product of heroically thorough research. Trudging through those acres of correspondence, speeches, pamphlets, periodicals and ephemera was presumably required for David Everatt’s Oxford DPhil dissertation awarded in 1990, entitled "The Politics of Non-Racialism: White Opposition to Apartheid, 1945-60". It would be interesting to compare the dissertation with the book under review published more than 25 years after the research was done. Curiously, ’The Politics of Non-Racialism’ is not among Everatt’s six publications in the book’s bibliography. The title of the book offers us the "origins" of non-racialism, and fails to define the term or to reveal its origin. The title of the dissertation similarly begs the question.